Low-cost 3D-printed adaptive suspension system for mobile robots using DMP-based real-time stabilization - Sumit Babu Rijal; Prasiddha Chaulagain; Suman Kandel; Tul Bahadur Saru; Srijana Pariyar; Yubraj Bajgain; Kiran Giri (Journal of Mechatronics, Electrical Power, and Vehicular Technology, 2025)
This paper presents a low-cost adaptive suspension system designed to stabilize a mobile robotic platform operating on uneven terrain. Unlike many existing low-cost servo-based suspension approaches that depend on software-intensive filtering, threshold logic, or extensive tuning, the proposed system adopts a simplified control strategy using hardware-level sensor fusion from the digital motion processor (DMP) of an MPU6050 IMU combined with direct angle-to-actuation mapping. The mechanical design is based on a four-bar linkage suspension architecture actuated by servo motors and controlled using an ESP32 microcontroller, enabling real-time compensation of pitch and roll disturbances. Developed as a proof-of-concept platform with modular 3D-printed components, the system emphasizes accessibility, ease of fabrication, and reduced control complexity. Experimental evaluation under controlled, quasi-static conditions demonstrates effective chassis stabilization with limited angular deviation and consistently lower noise compared to a Kalman filter-based implementation, particularly during post-calibration operation. By balancing mechanical simplicity and additive manufacturing with reliable orientation feedback, the proposed design provides an accessible framework for teaching laboratories, low-budget research, and early-stage adaptive suspension development in resource-constrained environments.